2013
DOI: 10.1007/s00221-013-3743-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of removal of invisible fixation on the saccadic and manual gap effect

Abstract: Saccadic and manual reactions to a peripherally presented target are facilitated by removing a central fixation stimulus shortly before a target onset (the gap effect). The present study examined the effects of removal of a visible and invisible fixation point on the saccadic gap effect and the manual gap effect. Participants were required to fixate a central fixation point and respond to a peripherally presented target as quickly and accurately as possible by making a saccade (Experiment 1) or pressing a corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…A gap effect has been demonstrated for manual reaction times (Ueda et al, 2014). This might explain the reduction in the perception reaction time that we observed in the gap condition.…”
Section: Saccade and Perception Reaction Times Depend On Tasupporting
confidence: 61%
See 1 more Smart Citation
“…A gap effect has been demonstrated for manual reaction times (Ueda et al, 2014). This might explain the reduction in the perception reaction time that we observed in the gap condition.…”
Section: Saccade and Perception Reaction Times Depend On Tasupporting
confidence: 61%
“…However, manual reaction times do not show an increase in latency during an overlap task. Indeed, it has been demonstrated that maintenance of a foveal stimulus does not increase the manual reaction time (Ueda et al, 2014). Thus, changes in the manual reaction time could not explain the increase of the perception reaction time in the overlap condition.…”
Section: Saccade and Perception Reaction Times Depend On Tamentioning
confidence: 98%
“…In the manual response task, we did not observe a significant facilitation effect of blue light on manual response as the saccadic response task did. However, it is not surprising as previous studies have suggested that the manual gap effect and the saccadic gap effect are driven by different factors (Jin & Reeves, 2009;Ueda, Takahashi, & Watanabe, 2014), where the manual gap effect is mainly driven by the general warning effect (Jin & Reeves, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…As previously discussed for our normal subjects, the perception report reaction time can be considered as resulting from two main components: the time to form the conscious perception and the time to plan and execute the button press (manual reaction time). Manual reaction times can be slightly shortened by a gap between stimuli, but they do not increase when there is an overlap . Therefore, we previously concluded that the perceptual report reaction time‐change dependence upon TA (shape of the curve) is mainly attributable to a dependence upon TA of the time to build the perception.…”
Section: Resultsmentioning
confidence: 92%
“…Manual reaction times can be slightly shortened by a gap between stimuli, but they do not increase when there is an overlap. 38 Therefore, we previously concluded that the perceptual report reaction time-change dependence upon TA (shape of the curve) is mainly attributable to a dependence upon TA of the time to build the perception. In PD, manual reaction time and movement execution are usually longer than normal.…”
Section: Saccade and Perceptual Reaction Timementioning
confidence: 96%